Dampak Korupsi terhadap Pembangunan Ekonomi dan Penegakan Hukum di Indonesia - Ayu Suraya; Afrijal Afrijal (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Corruption is an extraordinary crime that has multidimensional impacts on a country’s social, economic, and political life. In Indonesia, corruption cases not only cause financial losses to the state but also undermine public trust in the government and weaken the rule of law. This study examines the case of social assistance (bansos) corruption during the Covid-19 pandemic involving former Minister of Social Affairs, Juliari P. Batubara, who was proven to receive bribes from vendors providing social assistance amounting to tens of billions of rupiah. The study aims to understand the regulation of corruption under Indonesian law, the chronology of the bansos corruption case, and the criminal liability of the former Minister of Social Affairs. The analysis shows that this case not only caused financial losses to the state but also inflicted social suffering on the poor affected by the pandemic and reduced the government’s legitimacy. The prison sentence, fines, and obligation to pay state compensation imposed on Juliari affirm the principle of criminal accountability, while digital-based reform in social assistance distribution and multi-layered supervision serve as preventive measures to curb future corruption. This study emphasizes the importance of transparency, accountability, and strict law enforcement in combating corruption in Indonesia.